THE EFFECTS OF PROGRAMMED TRAINING ON FLEXIBILITY CHANGE OF CADET AGE FOOTBALL PLAYERS IN PERIOD OF 6 WEEKS - Jovan Gardašević; Duško Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The research was made on sample of 120 football players of cadet age, members of 4 football clubs from Niksic. The aim of research was to identify level of quantitive changes of variables for assessing the flexibility under the influence of football training. The training program included a 44 unit trainers during the summer period time of 6 weeks. Based on the results of t-test for dependent samples large, conclusion is that the training program produced statistically significant positive quantitative changes in all variables, for assessing the flexibility in this sample of player.